Threats to information security of state corporations of the Russian Federation - I. A. Loskutov; S. A. Reznichenko (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. Structuring of publicly available information to identify the distinctive features inherent in state corporations of the Russian Federation and to describe the threats arising as a result of their continuous operation.Method. The following methods of scientific cognition are used: systematization, description, analysis, deduction. The characteristics of state corporations are formed on the basis of data obtained both from the regulatory framework and by means of analysis of modern research in the field. In the future, the systematization of knowledge about the threats of state corporations is carried out, the most common classifications are considered, the increasing activity of intruders regarding critical information infrastructure objects is noted, and possible consequences for the state corporation after a successful computer attack on them are noted.Result. In this paper, a study was conducted on a little–covered area in the scientific literature - the protection of Russian state corporations. A comprehensive analysis made it possible to characterize the object of research in detail, thereby specifying the significant aspects of its functioning. Next, the most significant threats of Russian state corporations were shown, the importance of ensuring information security was noted and 15 factor influences of a successful cyberattack were shown.Conclusions. The conducted research is of an overview nature. The materials presented in the paper can serve as a basis for further research in the direction, as well as the formation of principles of protection against the mentioned threats.